Printing and book culture in late Imperial China - Brokaw, Cynthia Joanne; Chow, Kai-wing, 1951- (Studies on China ;, 2005)
Informed by insights from the rich literature on the history of the Western book, these essays investigate the relationship between the manuscript and print culture; the emergence of urban and rural publishing centres; the expanding audience for books; the development of niche markets and specialized publishing of fiction, drama, non-Han texts, and genealogies; and more.